Waste of the cassava in family agroindustries in the northeast Pará, Brazil - Souza, Fernanda Vanessa de Aragão; Ribeiro, Suezilde da Conceição do Amaral; Silva, Felix Lelis da; Teodosio, Albert Mathias (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Manihot esculenta Crantz represents one of the most important socioeconomic cultures in Brazil, since it plays a social role in the generation of employment and income of family farmers and communities, whose main source of income is in this activity. This process generates waste which, if not collected and treated properly, can cause damage to the environment. In the northeastern region of Pará there are several agri-food enterprises that benefit cassava. Thus, a study was carried out on the processing of cassava in agri-food enterprises in the northeast of Pará and the perception about the initiatives of the process of utilization of its residues. The research was conducted through field visits, interviews with farmers, and some photographic records. A questionnaire consisting of open and closed questions was applied, and the interviewees were chosen by means of the technique called snowball sampling. After the data collection, a quantitative evaluation was carried out, making it possible to detect that cassava beneficiation enterprises studied in the northeastern region of Pará do not adequately treat their residues and the most worrisome is the disposal of the manipueira (effluent), since it is considered a toxic solution, due to the presence of linamarin, glycoside, characteristic of the cassava plant, potentially hydrolyzed to hydrocyanic acid. Even being an organic material, due to improper packaging, can cause damage to the environment and public health.